Short-wavelength experiments on laser pulse interaction with extended pre-plasma at the PALS-installation. (18th December 2015) - Pisarczyk, T.; Gus'kov, S.Yu.; Renner, O.; Dudzak, R.; Dostal, J.; Demchenko, N.N.; Smid, M.; Chodukowski, T.; Kalinowska, Z.; Rosinski, M.; Parys, P.; Badziak, J.; et al.
Abstract: The paper is a continuation of research carried out at Prague Asterix Laser System (PALS) related to the shock ignition (SI) approach in inertial fusion, which was carried out with use of 1ω main laser beam as the main beam generating a shock wave. Two-layer targets were used, consisting of Cu massive planar target coated with a thin polyethylene layer, which, in the case of two-beam irradiation geometry, simulate conditions related to the SI scenario. The investigations presented in this paper are relate d to the use of 3ω to create ablation pressure for high-power shock wave generation. The interferometric studies of the ablative plasma expansion, complemented by measurements of crater volumes and K α emission, clearly demonstrate the effect of changing the incident laser intensity due to changing the focal radius on efficiency of laser energy transfer to a shock wave and fast electron emission. The efficiency of the energy transfer increases with the radius of the focused laser beam. The pre-plasma does not significantly change the character of this effect. However, it unambiguously results in the increasing temperature of fast electrons, the total energy of which remains very small (<0.1% of the laser energy). This study shows that the optimal radius from the point of view of 3ω radiation energy transfer to the shock wave is the maximal one used in these experiments and equal to 200 µm that corresponds to the minimal effect of two-dimensional (2D)-expansion. Such a result is typical for the ablation process determined by electron conductivity energy transfer under the conditions of one-dimensional or 2D matter expansion without any appreciable effect due to energy transfer by fast electrons. The 2D simulations based on application of the ALANT-HE code and an analytical model that includes generation and transport of hot electrons has been used to support of experimental data.